STRATEGI PENANGANAN LIMBAH INDUSTRI ALKALI TREATED COTTONII - Yuli Wibowo (Agroindustrial Technology, University of Trunojoyo Madura, 2012)
Thisstudyaims to formulate an alternative strategy in dealing with waste problems generated by the ATC industry, and predict to what extent these strategies can be effectively and efficiently handle the amount of waste there. The method used for analyzing includes analytical hierarchy process and heuristic methods. The results showed that the priority strategies that can be selected to handle the ATC waste was reusedthe waste water through the recycling process. Efficiency of water use through the recycling process reached 60.71%.